Double-shell calcium carbonate / calcium sulfide loaded charcoal adsorbent as well as preparation and application thereof
By loading the bicantilized calcium carbonate/calcium sulfide structure on kelp biochar, the problem of poor effect of primitive biochar in removing cadmium was solved, and efficient and stable cadmium adsorption was achieved, avoiding pollution and difficult-to-treat precipitation.
Patent Information
- Application Number
- CN202510330669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
In the prior art, the original biochar has limited effect in removing heavy metal cadmium (Cd), and cannot achieve efficient removal, resulting in environmental pollution.
Bihulled calcium carbonate/calcium sulfide (CaCO3/CaS)-loaded biochar adsorbents are used to jointly adsorb cadmium ions by loading CaS as the inner shell layer on the surface of kelp biochar.
A large cadmium (Cd) adsorption capacity is achieved, and the adsorption process is stable, which avoids the generation of difficult-to-treat floc precipitation. The preparation process is simple and the raw materials are easy to obtain, which is in line with the green preparation method.
Smart Images

Figure CN119838569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbents, and in particular to a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent and a preparation and application thereof. Background Art
[0002] There are many methods for treating wastewater containing Cd(Ⅱ), such as ion exchange, chemical precipitation and adsorption. Among them, adsorption technology has become the first choice because it is renewable, environmentally friendly, low-cost and has outstanding effects. Biochar has good application potential in the removal of heavy metals due to its rich porous structure and various functional groups. However, the adsorption effect of general original biochar is limited, and it is impossible to achieve efficient removal of heavy metal cadmium (Cd). Therefore, it is necessary to explore reasonable biochar modification strategies to adapt to complex wastewater environments and reduce the degree of pollution of heavy metal Cd(Ⅱ) to the environment. Summary of the invention
[0003] The purpose of the present invention is to provide a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent and its preparation and application, so as to solve the problems existing in the above-mentioned prior art.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is: a double-shell calcium carbonate / calcium sulfide (CaCO3 / CaS) loaded biochar adsorbent, wherein the double-shell calcium carbonate / calcium sulfide (CaCO3 / CaS) loaded biochar adsorbent has kelp biochar as a core, calcium sulfide (CaS) as an inner shell layer, and calcium carbonate (CaCO3) as an outer shell layer.
[0006] That is, the double-shell CaCO3 / CaS-loaded biochar adsorbent is based on kelp biochar, and a double-shell structure with CaS as the inner shell layer (or inner layer) and CaCO3 as the outer shell layer (or surface layer) is loaded on the surface of the kelp biochar.
[0007] The double-shell CaCO3 / CaS loaded biochar adsorbent of the present invention has a CaCO3 / CaS double-layer structure on its surface. The CaCO3 of the outer shell layer stabilizes the CaS of the inner shell layer (CaS has higher reaction activity due to its slight solubility, and can only stably perform adsorption in the inner layer under the protection of the CaCO3 of the outer shell layer, otherwise CaS will dissolve in water and generate flocculent precipitation that is difficult to handle with Cd(II)). The inner and outer shell layers simultaneously interact with cadmium ions during the adsorption process (in the process of Cd(II) diffusing into the biochar, a part of it is first adsorbed by the CaCO3 on the surface, and the unadsorbed part of Cd(II) enters the inner layer of CaS and continues to be adsorbed). Based on the synergistic adsorption effect of CaCO3 / CaS, the double-shell CaCO3 / CaS loaded biochar adsorbent of the present invention has a large Cd(II) adsorption capacity.
[0008] The second technical solution of the present invention: The preparation method of the above-mentioned double-shell calcium carbonate / calcium sulfide (CaCO3 / CaS) loaded biochar adsorbent comprises the following steps:
[0009] Calcium sulfite (CaSO3) is used to pretreat kelp powder to obtain pretreated kelp particles; the pretreated kelp particles are carbonized to obtain calcium oxide / calcium sulfide (CaO / CaS)-loaded biochar; the calcium oxide / calcium sulfide (CaO / CaS)-loaded biochar is subjected to a first aging treatment to obtain calcium hydroxide / calcium sulfide (Ca(OH)2 / CaS)-loaded biochar; the calcium hydroxide / calcium sulfide (Ca(OH)2 / CaS)-loaded biochar is subjected to a second aging treatment to obtain the double-shell calcium carbonate / calcium sulfide (CaCO3 / CaS)-loaded biochar adsorbent.
[0010] The present invention firstly captures the insoluble CaSO3 and stably disperses it on the kelp powder through the action of sodium alginate (SA) rich in kelp, thereby obtaining pretreated kelp particles. Next, in the process of carbonizing the pretreated kelp particles, the kelp powder is converted into reducing biochar, and under high temperature environment, the CaSO3 on the surface of the kelp powder and the reducing biochar have a distance limit, so that the inner layer of the CaSO3 in contact with the reducing biochar is reduced to CaS, while the outer layer of the CaSO3 is converted into CaO at high temperature, thereby obtaining CaO / CaS loaded biochar with a double layer of CaO and CaS loaded on the surface (CaO layer is the surface layer, and CaS layer is the inner layer). Next, in the first aging process (artificial aging process), in a high humidity environment of 105°C (relative humidity of 80-90%), the CaO layer on the surface of the CaO / CaS loaded biochar can be fully converted into Ca(OH)2, thereby obtaining Ca(OH)2 / CaS loaded biochar. During the further second aging treatment (natural aging treatment), the Ca(OH)2 on the surface of the Ca(OH)2 / CaS-loaded biochar was further converted into CaCO3, and finally a double-shell CaCO3 / CaS-loaded biochar adsorbent with a double-layer load of CaCO3 and CaS on the surface (the CaCO3 layer is the surface layer and the CaS layer is the inner layer) was obtained (the two-step aging process only converts the CaO on the surface into CaCO3).
[0011] The sodium alginate rich in kelp causes the CaSO3 to be evenly and stably dispersed on the kelp powder, so that the subsequently prepared CaO / CaS-loaded biochar and CaCO3 / CaS-loaded biochar adsorbents both show the characteristics of uniform dispersion of surface loads, which can provide more adsorption sites on the adsorbent surface.
[0012] Furthermore, the method of pretreating kelp powder with CaSO3 to obtain pretreated kelp particles includes: adding kelp powder to a CaSO3 suspension, mixing under ultrasound and stirring for 30 to 90 minutes to obtain a mixed solution, and then drying the mixed solution to obtain the pretreated kelp particles.
[0013] Furthermore, the CaSO3 suspension is prepared by mixing CaSO3 and water in a dosage ratio of 1-2 g:100-200 mL.
[0014] Furthermore, the mass ratio of the kelp powder to the CaSO3 in the CaSO3 suspension is 10 g:1~2 g.
[0015] Further preferably, the CaSO3 suspension is prepared from CaSO3 and water in a dosage ratio of 2 g:125 mL; the mass ratio of the kelp powder to the CaSO3 in the CaSO3 suspension is 10:2; and the mixing time under ultrasound and stirring is 30 min.
[0016] Furthermore, the temperature of drying the mixed solution is 50-80°C.
[0017] Further preferably, the temperature for drying the mixed solution is 65° C. and the time is 10 h.
[0018] Furthermore, the carbonization conditions include: a holding temperature of 600-800° C. and a holding time of 30-90 min.
[0019] Furthermore, the carbonization conditions also include: a heating rate of 5-10 °C / min.
[0020] Furthermore, the carbonization is carried out under an inert gas atmosphere; the inert gas is preferably nitrogen.
[0021] Further preferably, the carbonization conditions include: a heating rate of 5°C / min, a holding temperature of 700°C, and a holding time of 60 min.
[0022] During the high-temperature carbonization process, the CaSO3 on the surface of the kelp biochar carrier reacts with the reduced carbon on the carrier at high temperature to form CaS, while the unreduced CaSO3 on the surface forms CaO under high temperature conditions. Therefore, the control of the carbonization temperature is particularly important. The reactions occurring in the inner and outer layers during the carbonization process are as follows:
[0023] Inner layer: 2CaSO3 + 3C → 2CaS + 3CO2↑;
[0024] Outer layer: CaSO3 → CaO + SO2↑.
[0025] Furthermore, the first aging treatment step includes placing the CaO / CaS-loaded biochar in a 105° C. water vapor environment for 8 to 16 hours.
[0026] Further preferably, the CaO / CaS-loaded biochar is placed in a 105° C. water vapor environment for 12 to 16 hours.
[0027] Furthermore, the 105°C water vapor environment is a high humidity environment with a relative humidity of 80-90%.
[0028] Furthermore, the second aging treatment step includes placing the Ca(OH)2 / CaS-loaded biochar at 20-30°C for 7 days.
[0029] Furthermore, there is no special requirement for the environmental humidity during the second aging treatment, and the Ca(OH)2 / CaS-loaded organisms can be placed in an indoor natural environment at 20-30°C for 7 days.
[0030] Furthermore, the preparation step of the kelp powder includes: washing the kelp with water to remove impurities, soaking the kelp in water for 24 hours, and then drying and crushing to obtain the kelp powder.
[0031] Furthermore, the drying temperature is 50-80°C and the drying time is 8-48 h.
[0032] More preferably, the drying temperature is 65° C. and the drying time is 24 h.
[0033] The third technical solution of the present invention: Application of the above double-shell CaCO3 / CaS-loaded biochar adsorbent in adsorbing Cd(II) in wastewater.
[0034] The present invention discloses the following technical effects:
[0035] (1) The double-shell CaCO3 / CaS-loaded biochar adsorbent of the present invention has a CaCO3 / CaS double-layer structure on its surface. Based on the synergistic adsorption effect of CaCO3 / CaS, the double-shell CaCO3 / CaS-loaded biochar adsorbent has a large Cd(II) adsorption capacity.
[0036] (2) The surface layer of the double-shell CaCO3 / CaS-loaded biochar adsorbent of the present invention is a CaCO3 shell layer, which can effectively prevent the dissolution of alkaline substances such as internal CaS, thereby making the adsorption process stable and preventing the formation of flocculent precipitation that is difficult to handle during the adsorption process.
[0037] (3) The raw materials of the double-shell CaCO3 / CaS-loaded biochar adsorbent of the present invention are easily available, the preparation process is simple, no toxic or harmful reagents are used in the preparation process, and the green preparation method is adopted, which is conducive to the production of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 The schematic diagram of the preparation principle and process of the double-shell CaCO3 / CaS loaded biochar adsorbent of the present invention;
[0040] Figure 2 Schematic diagram of the homemade device used in step (2) of Examples 1-3;
[0041] Figure 3 SEM images of the CaO / CaS-loaded biochar (the product of step (3)) and the double-shell CaCO3 / CaS-loaded biochar adsorbent (the product of step (5)) in Example 1 and the calcium-loaded rice straw biochar CAC@Ca in Comparative Example 1;
[0042] Figure 4 The energy spectrum diagram of the distribution of S and Ca elements corresponding to the SEM images of the CaO / CaS-loaded biochar (the product of step (3)) in Example 1 and the calcium-loaded rice straw biochar CAC@Ca in Comparative Example 1;
[0043] Figure 5 The CaO / CaS-loaded biochar (KAC@CaS-CaO) and Ca(OH)2 / CaS-loaded biochar (KAC 12 @CaS-Ca(OH)2) and double-shell CaCO3 / CaS loaded biochar adsorbent (KAC 12 @CaS-CaCO3) XRD pattern;
[0044] Figure 6 The CaO / CaS-loaded biochar (KAC@CaS-CaO) and Ca(OH)2 / CaS-loaded biochar (KAC 12 @CaS-Ca(OH)2) and double-shell CaCO3 / CaS loaded biochar adsorbent (KAC 12 @CaS-CaCO3) Fourier transform infrared spectrum;
[0045] Figure 7 The CaO / CaS-loaded biochar (KAC@CaS-CaO) and Ca(OH)2 / CaS-loaded biochar (KAC 12 @CaS-Ca(OH)2) and double-shell CaCO3 / CaS loaded biochar adsorbent (KAC 12 @CaS-CaCO3) in the X-ray photoelectron spectrum of sulfur element S 2p;
[0046] Figure 8 The double-shell CaCO3 / CaS-loaded biochar adsorbent (KAC8@CaS-CaCO3, KAC 12 @CaS-CaCO3, KAC 16 @CaS-CaCO3) and the unloaded aged kelp biochar KC obtained in comparative example 212 The curve of adsorption capacity changing with time;
[0047] Fig. 9 The double-shell CaCO3 / CaS-loaded biochar adsorbent (KAC8@CaS-CaCO3, KAC 12 @CaS-CaCO3, KAC 16 @CaS-CaCO3) and CaO / CaS loaded biochar (KAC@CaS-CaO) at the end point of adsorption in Cd(Ⅱ) wastewater. DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0053] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0054] As a first aspect of the present invention, the present invention provides a double-shell CaCO3 / CaS-loaded biochar adsorbent, wherein the double-shell CaCO3 / CaS-loaded biochar adsorbent has kelp biochar as a core, CaS as an inner shell layer, and CaCO3 as an outer shell layer.
[0055] As a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned double-shell CaCO3 / CaS-loaded biochar adsorbent (the preparation principle and process diagram are as follows Figure 1 ), including the following steps:
[0056] Kelp powder is pretreated with CaSO3 to obtain pretreated kelp particles (i.e., kelp particles loaded with CaSO3); the pretreated kelp particles are carbonized to obtain CaO / CaS loaded biochar; the CaO / CaS loaded biochar is subjected to a first aging treatment to obtain Ca(OH)2 / CaS loaded biochar; the Ca(OH)2 / CaS loaded biochar is subjected to a second aging treatment to obtain the double-shell CaCO3 / CaS loaded biochar adsorbent.
[0057] As an embodiment of the present invention, the method of pretreating kelp powder with CaSO3 to obtain pretreated kelp particles includes: adding kelp powder to a CaSO3 suspension, mixing under ultrasound and stirring for 30 to 90 minutes to obtain a mixed solution, and then drying the mixed solution to obtain the pretreated kelp particles.
[0058] As an embodiment of the present invention, the CaSO3 suspension is prepared by mixing CaSO3 and water in a dosage ratio of 1-2 g:100-200 mL.
[0059] As an embodiment of the present invention, the mass ratio of the kelp powder to the CaSO3 in the CaSO3 suspension is 10 g:1~2 g.
[0060] As a preferred embodiment of the present invention, the CaSO3 suspension is prepared by CaSO3 and water in a dosage ratio of 2 g:125 mL; the mass ratio of the kelp powder to the CaSO3 in the CaSO3 suspension is 10:2; and the mixing time under ultrasound and stirring is 30 min.
[0061] As an embodiment of the present invention, the temperature for drying the mixed solution is 50-80°C, preferably 65°C, and the time is 10 h.
[0062] As an embodiment of the present invention, the carbonization conditions include: a heating rate of 5-10°C / min, a holding temperature of 600-800°C, and a holding time of 30-90 min.
[0063] As an embodiment of the present invention, the carbonization is performed under an inert gas atmosphere; the inert gas is preferably nitrogen.
[0064] As a preferred embodiment of the present invention, the carbonization conditions include: a heating rate of 5°C / min, a holding temperature of 700°C, and a holding time of 60 min.
[0065] As an embodiment of the present invention, the first aging treatment step comprises: placing the CaO / CaS-loaded biochar in a 105° C. water vapor environment for 8 to 16 hours, preferably for 12 to 16 hours.
[0066] As an embodiment of the present invention, the 105° C. water vapor environment is a high humidity environment with a relative humidity of 80-90%.
[0067] As a preferred embodiment of the present invention, the first aging treatment is carried out in a device capable of producing a high humidity environment. Figure 2 The homemade device shown is used as a device to generate a high humidity environment. Figure 2 The device shown can maintain the sample in a high humidity environment and can achieve an ambient temperature of 105°C by placing the device in an oven. Figure 2 The principle of the device shown is as follows: at an ambient temperature of 105 °C, while the CaO / CaS loaded biochar is heated, the water in the container beaker is also heated and evaporated, and the generated water vapor ages the CaO / CaS loaded biochar placed in the liner (i.e., promotes the surface CaO to convert to Ca(OH)2), thereby creating a high humidity heating environment to age the biochar; in addition, to prevent the humidity from being too high, the top cover of the container is provided with a through hole to discharge part of the water vapor, so that the relative humidity in the liner is always maintained at 80-90%. The device used in the first aging treatment is not a limitation of the present invention, and any other device that can generate a high humidity environment can be selected, as long as the sample is aged in a high humidity environment of 105 °C (relative humidity of 80-90%). The high humidity environment can fully convert the CaO layer on the surface of the CaO / CaS loaded biochar into Ca(OH)2, which is conducive to the formation of the CaCO3 layer during the second aging treatment (natural aging treatment).
[0068] As an embodiment of the present invention, the second aging treatment step includes: placing the Ca(OH)2 / CaS-loaded biochar at 20-30°C for 7 days.
[0069] As an embodiment of the present invention, there is no special requirement for the environmental humidity during the second aging treatment process, and the Ca(OH)2 / CaS-loaded organisms can be placed in an indoor natural environment at 20-30°C for 7 days.
[0070] As an embodiment of the present invention, the preparation steps of the kelp powder include: washing the kelp with water to remove impurities, soaking the kelp in water for 24 hours, and then drying and crushing to obtain the kelp powder.
[0071] As an embodiment of the present invention, the drying temperature is 50-80° C. and the drying time is 8-48 h.
[0072] As a preferred embodiment of the present invention, the drying temperature is 65° C. and the drying time is 24 h.
[0073] As a third aspect of the present invention, the present invention provides the use of the above-mentioned double-shell CaCO3 / CaS-loaded biochar adsorbent in the adsorption of Cd(II) in wastewater.
[0074] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0075] The room temperature involved in the specific implementation mode of the present invention specifically refers to 20~30℃;
[0076] All raw materials used in the specific embodiments of the present invention are purchased from commercial sources.
[0077] Example 1
[0078] A double-shell CaCO3 / CaS loaded biochar adsorbent, the preparation steps are as follows:
[0079] (1) After washing and removing impurities from the kelp, soak it in water for 24 h, take it out and dry it at 65°C for 24 h, then grind it and pass it through an 80-mesh sieve to obtain kelp powder.
[0080] (2) Take 10 g of the kelp powder obtained in step (1) and add it to the ultrasonically dispersed CaSO3 suspension, where the ratio of CaSO3 to deionized water in the CaSO3 suspension is 2 g:125 mL. Mix it for 30 min under ultrasonic and mechanical stirring (ultrasonic power of 100 W, speed of 800 rpm) to obtain a mixed solution, which is then dried at 65 °C for 10 h and ground to obtain pretreated kelp particles.
[0081] (3) The pretreated kelp particles obtained in step (2) were carbonized at 700 °C under a nitrogen atmosphere. The heating rate of the tubular furnace used was 5 °C / min and the holding time was 60 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain CaO / CaS-loaded biochar, which was named KAC@CaS-CaO.
[0082] (4) The CaO / CaS-loaded biochar obtained in step (3) is placed in a homemade device (the schematic diagram of the homemade device is shown in FIG. Figure 2 The device was placed in a 105 °C oven and reacted for 12 h at 105 °C and in a high humidity environment (relative humidity of 80-90%) to obtain Ca(OH)2 / CaS-loaded biochar, which was named KAC. 12 @CaS-Ca(OH)2.
[0083] (5) The Ca(OH)2 / CaS-loaded biochar obtained in step (4) was placed in an indoor natural environment at 20-30°C for 7 days to obtain a double-shell CaCO3 / CaS-loaded biochar adsorbent, which was named KAC 12 @CaS-CaCO3.
[0084] Example 2
[0085] A double-shell CaCO3 / CaS loaded biochar adsorbent, the preparation steps are as follows:
[0086] (1) After washing and removing impurities from the kelp, soak it in water for 24 h, take it out and dry it at 65°C for 24 h, then grind it and pass it through an 80-mesh sieve to obtain kelp powder.
[0087] (2) Take 10 g of the kelp powder obtained in step (1) and add it to the ultrasonically dispersed CaSO3 suspension, where the ratio of CaSO3 to deionized water in the CaSO3 suspension is 2 g:125 mL. Mix it for 30 min under ultrasonic and mechanical stirring (ultrasonic power of 100 W, speed of 800 rpm) to obtain a mixed solution, which is then dried at 65 °C for 10 h and ground to obtain pretreated kelp particles.
[0088] (3) The pretreated kelp particles obtained in step (2) were carbonized at 700 °C under a nitrogen atmosphere. The heating rate of the tubular furnace used was 5 °C / min and the holding time was 60 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain CaO / CaS-loaded biochar, which was named KAC@CaS-CaO.
[0089] (4) The CaO / CaS-loaded biochar obtained in step (3) is placed in a homemade device (the schematic diagram of the homemade device is shown in FIG. Figure 2As shown in the figure, the device was placed in a 105 °C oven and reacted at 105 °C and a high humidity environment (relative humidity of 80-90%) for 8 h to obtain Ca(OH)2 / CaS-loaded biochar, which was named KAC8@CaS-Ca(OH)2.
[0090] (5) The Ca(OH)2 / CaS-loaded biochar obtained in step (4) was placed in an indoor natural environment at 20-30°C for 7 days to obtain a double-shell CaCO3 / CaS-loaded biochar adsorbent, which was named KAC8@CaS-CaCO3.
[0091] Example 3
[0092] A double-shell CaCO3 / CaS loaded biochar adsorbent, the preparation steps are as follows:
[0093] (1) After washing and removing impurities from the kelp, soak it in water for 24 h, take it out and dry it at 65°C for 24 h, then grind it and pass it through an 80-mesh sieve to obtain kelp powder.
[0094] (2) Take 10 g of the kelp powder obtained in step (1) and add it to the ultrasonically dispersed CaSO3 suspension, where the ratio of CaSO3 to deionized water in the CaSO3 suspension is 2 g:125 mL. Mix it for 30 min under ultrasonic and mechanical stirring (ultrasonic power of 100 W, speed of 800 rpm) to obtain a mixed solution, which is then dried at 65 °C for 10 h and ground to obtain pretreated kelp particles.
[0095] (3) The pretreated kelp particles obtained in step (2) were carbonized at 700 °C under a nitrogen atmosphere. The heating rate of the tubular furnace used was 5 °C / min and the holding time was 60 min. After the reaction was completed, the mixture was naturally cooled to room temperature to obtain CaO / CaS-loaded biochar, which was named KAC@CaS-CaO.
[0096] (4) The CaO / CaS-loaded biochar obtained in step (3) is placed in a homemade device (the schematic diagram of the homemade device is shown in FIG. Figure 2 The device was placed in a 105 °C oven and reacted for 16 h at 105 °C and in a high humidity environment (relative humidity of 80-90%) to obtain Ca(OH)2 / CaS-loaded biochar, which was named KAC. 16 @CaS-Ca(OH)2.
[0097] (5) The Ca(OH)2 / CaS-loaded biochar obtained in step (4) was placed in an indoor natural environment at 20-30°C for 7 days to obtain a double-shell CaCO3 / CaS-loaded biochar adsorbent, which was named KAC 16@CaS-CaCO3.
[0098] Comparative Example 1
[0099] A calcium-loaded rice straw biochar, the preparation steps are as follows:
[0100] (1) After washing and removing impurities from rice straw, the rice straw was soaked in water for 24 h, taken out and dried at 65 °C for 24 h, and then crushed and passed through an 80-mesh sieve to obtain rice straw powder.
[0101] (2) Take 10 g of the rice straw powder obtained in step (1) and add it to the ultrasonically dispersed CaSO3 suspension, where the ratio of CaSO3 to deionized water in the CaSO3 suspension is 2 g:125 mL. Mix it for 30 min under ultrasonic and mechanical stirring (ultrasonic power of 100 W, speed of 800 rpm) to obtain a mixed solution, which is then dried at 65 °C for 10 h and ground to obtain pretreated rice straw particles.
[0102] (3) The pretreated rice straw particles obtained in step (2) were carbonized at 700 °C under a nitrogen atmosphere. The heating rate of the tubular furnace used was 5 °C / min and the insulation time was 60 min. After the reaction was completed, the particles were naturally cooled to room temperature to obtain calcium-loaded rice straw biochar, which was named CAC@Ca.
[0103] Comparative Example 2
[0104] Unloaded aged kelp biochar was prepared as follows:
[0105] (1) After washing and removing impurities from the kelp, soak it in water for 24 h, take it out and dry it at 65°C for 24 h, then grind it and pass it through an 80-mesh sieve to obtain kelp powder.
[0106] (2) The kelp powder obtained in step (1) was carbonized at 700 °C under a nitrogen atmosphere. The heating rate of the tubular furnace used was 5 °C / min and the holding time was 60 min. After the reaction was completed, it was naturally cooled to room temperature to obtain kelp biochar, which was named KC.
[0107] (3) Place the kelp biochar obtained in step (2) in a self-made device (the schematic diagram of the self-made device is shown in FIG. Figure 2 The device was placed in a 105 °C oven and reacted at 105 °C and a high humidity environment (relative humidity of 80-90%) for 12 h.
[0108] (4) The product after the reaction in step (3) was placed in an indoor natural environment at 20-30°C for 7 days to obtain unloaded aged kelp biochar, which was named KC 12 .
[0109] Test Example 1
[0110] Morphology and composition characterization
[0111] 1. SEM analysis
[0112] The CaO / CaS loaded biochar KAC@CaS-CaO (the product of step (3)) in Example 1 and the double-shell CaCO3 / CaS loaded biochar adsorbent KAC 12 @CaS-CaCO3 (the product of step (5)) and the calcium-loaded rice straw biochar CAC@Ca sample in comparative example 1 were blown onto the conductive glue using an ear bulb and adhered to the SEM sample stage. The samples were then gold-sprayed to prevent surface charge accumulation from affecting the imaging quality. After being transferred to a sample chamber and evacuated, they were ion sputtered for 30 seconds. The samples were photographed using a JSM-7800FPrime SEM with a magnification range of 25-1000000 times. The results are shown in Figure 2. Figure 3 shown.
[0113] Depend on Figure 3 It can be seen that the two types of loaded biochar in Example 1 (KAC@CaS-CaO and KAC 12 @CaS-CaCO3) have evenly distributed fine particles on the surface, which shows that the method of Example 1 can effectively prepare biochar with uniform CaO / CaS loading, and the distribution of the loading material remains almost unchanged during the first aging treatment (artificial aging treatment) and the second aging treatment (natural aging treatment). The evenly dispersed fine CaCO3 / CaS particles can provide abundant adsorption sites for the CaCO3 / CaS-loaded biochar adsorbent to increase its adsorption capacity for Cd(Ⅱ). The surface of the calcium-loaded rice straw biochar CAC@Ca in Comparative Example 1 is aggregated and larger spherical particles, which shows that kelp as a raw material has a significant effect on the uniform distribution of the loading material during the loading process, while rice straw as a raw material does not have this effect.
[0114] 2. SEM-EDS analysis
[0115] For example Figure 3 The distribution of S and Ca elements in the samples CaO / CaS-loaded biochar KAC@CaS-CaO (the product of step (3) of Example 1) and calcium-loaded rice straw biochar CAC@Ca (Comparative Example 1) under SEM observation was analyzed using a scanning electron microscope / energy dispersive spectrometer (IE250X-Max50, Germany). The results are as follows: Figure 4 shown.
[0116] Depend on Figure 4It can be seen that the S and Ca elements of the CaO / CaS-loaded biochar KAC@CaS-CaO in Example 1 are evenly distributed, that is, the CaO / CaS loaded on the surface is evenly distributed. This is mainly due to the role of sodium alginate in kelp. As a stabilizer for nanoparticles, sodium alginate can effectively capture and stabilize the ultrasonically dispersed CaSO3 particles during the pretreatment process of step (2) of Example 1, which makes the CaO / CaS on the surface of the product KAC@CaS-CaO obtained after carbonization have good dispersibility. In addition, compared with the uniform distribution of S elements on the surface of KAC@CaS-CaO, the distribution of Ca elements shows the characteristics of granular strong signal distribution. These strong Ca element signals come from CaO produced by the pyrolysis of CaSO3 on the surface that is not in contact with the reducing carbon. Therefore, it is preliminarily confirmed that the surface of KAC@CaS-CaO is composed of a double shell of CaO and CaS. However, the S and Ca elements of the calcium-loaded rice straw biochar CAC@Ca in Comparative Example 1 are unevenly distributed, and match the distribution of the spherical particles on the surface in the corresponding SEM image, which further illustrates that using rice straw as a raw material does not have the function of evenly distributing the load.
[0117] 3. XRD analysis
[0118] The CaO / CaS-loaded biochar KAC@CaS-CaO (the product of step (3)) and Ca(OH)2 / CaS-loaded biochar KAC 12 @CaS-Ca(OH)2 (product of step (4)) and double-shell CaCO3 / CaS loaded biochar adsorbent KAC 12 @CaS-CaCO3 (the product of step (5)) was characterized by X-ray diffractometer (XRD, Smartlab SE, Rigaku, Japan). Figure 5 shown.
[0119] Depend on Figure 5 It can be seen that KAC@CaS-CaO, KAC 12 @CaS-Ca(OH)2 and KAC 12 Significant characteristic diffraction peaks of CaS can be observed in the XRD spectra of @CaS-CaCO3. During the aging process from step (4) to step (5) of Example 1, the CaO on the surface of KAC@CaS-CaO is transformed from CaO to Ca(OH)2 and then to CaCO3. The rapid aging process has little effect on the CaS in the inner layer.
[0120] 4. FTIR analysis
[0121] The CaO / CaS loaded biochar KAC@CaS-CaO and Ca(OH)2 / CaS loaded biochar KAC in Example 1 12 @CaS-Ca(OH)2 and double-shell CaCO3 / CaS loaded biochar adsorbent KAC 12 @CaS-CaCO3 were analyzed for material composition using Fourier transform infrared spectroscopy (FTIR, VERTEX 70, Bruker). The results are as follows: Figure 6 shown.
[0122] from Figure 6 It can be clearly observed that after the first aging treatment (artificial aging treatment) of the sample CaO / CaS loaded biochar (KAC@CaS-CaO), the Ca(OH)2 / CaS loaded biochar (KAC 12 @CaS-Ca(OH)2) in FTIR at 3638 cm -1 The peak of Ca(OH)2 showed obvious characteristic peaks, and the CaCO3 / CaS loaded biochar adsorbent (KAC 12 @CaS-CaCO3) was not found. This further illustrates the process of CaO converting to Ca(OH)2 and then to CaCO3.
[0123] 5. Elemental analysis
[0124] The CaO / CaS loaded biochar KAC@CaS-CaO and Ca(OH)2 / CaS loaded biochar KAC in Example 1 12 @CaS-Ca(OH)2 and double-shell CaCO3 / CaS loaded biochar adsorbent KAC 12 @CaS-CaCO3 samples were subjected to elemental analysis, and the results are shown in Table 1.
[0125] Table 1 Changes in element content of samples before and after aging
[0126]
[0127] It can be seen from Table 1 that the S content changes slightly during the aging process. Combined with the introduction of C and O elements during the aging process, the total mass of the sample increases, and the S element can be considered to have little change.
[0128] 6. Analysis of sulfur S 2p spectrum in XPS
[0129] The CaO / CaS loaded biochar KAC@CaS-CaO and Ca(OH)2 / CaS loaded biochar KAC in Example 1 12 @CaS-Ca(OH)2 and double-shell CaCO3 / CaS loaded biochar adsorbent KAC12 @CaS-CaCO3 was analyzed by X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB 250XI) for S 2p spectrum. The results are as follows: Figure 7 shown.
[0130] Since the effective test depth of XPS is approximately 2 nm, this analysis mainly characterizes the surface S element composition. 12 @CaS-Ca(OH)2 and KAC 12 @The S 2p spectrum of CaS-CaCO3 shows that the aging process has a greater impact on the surface sulfur compounds, KAC 12 @CaS-Ca(OH)2 and KAC 12 @CaS-CaCO3 basically does not contain CaS. Combining the results of XRD and elemental analysis, it is shown that after the aging process, a small amount of CaS exposed on the surface disappears, while the overall CaS loss is small and mainly concentrated in the inner layer of the double shell.
[0131] Therefore, it can be confirmed that the CaCO3 / CaS-loaded biochar adsorbent obtained in step (5) of Example 1 has a CaCO3 / CaS double-layer loading structure, that is, a double-shell structure. This allows the CaCO3 / CaS loaded on the surface to play a synergistic adsorption role during the Cd(II) adsorption process, thereby effectively improving the adsorption capacity of the CaCO3 / CaS-loaded biochar adsorbent.
[0132] Test Example 2
[0133] Adsorption performance test
[0134] 1. Adsorption capacity of double-shell CaCO3 / CaS loaded biochar adsorbents with different aging times and unloaded aged kelp biochar
[0135] Cadmium nitrate was dissolved in deionized water with a pH of 5 to obtain an aqueous solution with a cadmium concentration of 200 mg / L. 20 mg of double-shell CaCO3 / CaS loaded biochar adsorbent was weighed into a 125 mL conical flask, and 50 mL of an aqueous solution with a cadmium concentration of 200 mg / L was added. The solution was placed in a water bath constant temperature oscillator and shaken thoroughly at 25 °C and 150 rpm. Samples were taken at 0 min, 10 min, 30 min, 60 min, 90 min, 120 min, 360 min, 600 min, 1200 min, 1800 min, and 3000 min, and the Cd(Ⅱ) concentration in the adsorbed solution was determined by atomic flame absorption spectrometry to calculate the adsorption capacity of the adsorbent.
[0136] Figure 8 The double-shell CaCO3 / CaS-loaded biochar adsorbent KAC8@CaS-CaCO3, KAC 12 @CaS-CaCO3, KAC 16 @CaS-CaCO3 and unloaded aged kelp biochar KC prepared in comparative example 2 12 The adsorption capacity of KAC8@CaS-CaCO3 and KAC 12 @CaS-CaCO3, KAC 16 @CaS-CaCO3 and KC 12 The maximum adsorption capacities were 435.2 mg / g, 386.4 mg / g, 297.2 mg / g and 16.0 mg / g respectively.
[0137] 2. Adsorption endpoint states of CaO / CaS loaded biochar and double-shell CaCO3 / CaS loaded biochar adsorbents
[0138] The double-shell CaCO3 / CaS-loaded biochar adsorbents KAC8@CaS-CaCO3 and KAC 12 @CaS-CaCO3, KAC 16 @CaS-CaCO3 and the CaO / CaS-loaded biochar KAC@CaS-CaO in Example 1 were taken out and placed in an ampoule to take digital photos after being adsorbed in the above-mentioned aqueous solution with a cadmium concentration of 200 mg / L for 3000 min (other adsorption conditions were the same as the above-mentioned adsorption capacity test process) to study their states at the adsorption end point. The results are as follows Fig. 9 shown.
[0139] Depend on Fig. 9 It can be seen that since the CaO loaded on the CaO / CaS-loaded biochar KAC@CaS-CaO is easily soluble and has strong alkalinity, a large amount of flocculent precipitate that is difficult to handle is formed after adsorption, and the precipitate is yellow, which comes from the CdS formed by the reaction of CaS with Cd(Ⅱ) after dissolution; and the double-shell CaCO3 / CaS-loaded biochar adsorbent has a good protective effect on the inner layer CaS because the surface layer is insoluble CaCO3. The double-shell CaCO3 / CaS-loaded biochar adsorbents with different aging times are significantly better than CaO / CaS-loaded biochar after adsorption. Specifically, a small amount of flocculent precipitate is produced after KAC8@CaS-CaCO3 adsorption, and the adsorbent is difficult to settle and disperse in the solution, while KAC 12 @CaS-CaCO3 and KAC 16@CaS-CaCO3 hardly forms flocculent precipitates that are difficult to handle, and can be separated from the solution by filtration. From the above conclusions, it can be seen that regulating the aging treatment time of step (4) of Example 1-3 can effectively improve the adsorption behavior during the adsorption process, effectively avoid the generation of flocculent precipitates that are difficult to handle, and facilitate the separation of the adsorbent from the solution, which is beneficial for the actual Cd(II) treatment process. It further illustrates that the prepared double-shell CaCO3 / CaS-loaded biochar adsorbent is a promising adsorbent.
[0140] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent, characterized in that: The double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent has kelp biochar as a core, calcium sulfide as an inner shell layer, and calcium carbonate as an outer shell layer.
2. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 1, characterized in that: The following steps are involved: Calcium sulfite is used to pretreat kelp powder to obtain pretreated kelp particles; the pretreated kelp particles are carbonized to obtain calcium oxide / calcium sulfide loaded biochar; the calcium oxide / calcium sulfide loaded biochar is subjected to a first aging treatment to obtain calcium hydroxide / calcium sulfide loaded biochar; the calcium hydroxide / calcium sulfide loaded biochar is subjected to a second aging treatment to obtain the double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent.
3. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 2, characterized in that: The method of pretreating kelp powder with calcium sulfite to obtain pretreated kelp particles comprises: adding kelp powder to a calcium sulfite suspension, mixing under ultrasound and stirring for 30 to 90 minutes to obtain a mixed solution, and then drying the mixed solution to obtain the pretreated kelp particles.
4. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 3, characterized in that: The calcium sulfite suspension is prepared by mixing calcium sulfite and water in a dosage ratio of 1-2 g:100-200 mL.
5. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 3, characterized in that: The mass ratio of the kelp powder to the calcium sulfite in the calcium sulfite suspension is 10:1-2.
6. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 2, characterized in that: The carbonization conditions include: a holding temperature of 600-800°C and a holding time of 30-90 min.
7. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 2, characterized in that: The first aging treatment step includes placing the calcium oxide / calcium sulfide loaded biochar in a 105° C. water vapor environment for 8 to 16 hours.
8. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 2, characterized in that: The second aging treatment step includes placing the calcium hydroxide / calcium sulfide loaded biochar at 20-30° C. for 7 days.
9. The method for preparing a double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent according to claim 2, characterized in that: The preparation steps of the kelp powder include: washing the kelp with water to remove impurities, soaking the kelp in water for 24 hours, and then drying and crushing to obtain the kelp powder.
10. Use of the double-shell calcium carbonate / calcium sulfide loaded biochar adsorbent as claimed in claim 1 in adsorbing Cd(II) in wastewater.
Citation Information
Patent Citations
Sodium alginate and calcium ion modified charcoal composite material as well as preparation method and application thereof
CN107983314A
Calcium alginate gel bead with shell of porous calcium carbonate microsphere and its preparing method
CN1985995A
Semiconductor memory device and manufacturing method thereof
KR102738779B1
Sodium alginate-gelatin based biochar multivariate composite material, preparation method therefor and method for removing cadmium in water bodies
US12030033B1
Method for preparing selenium-enriched modified biochar used for adsorbing cadmium
WO2024007797A1
Cited By
Efficient-adsorption underwater ecological dredging material and preparation method thereof
CN121648891A
Efficient adsorption of the water bottom ecological dredging material and preparation method thereof
CN121648891B